Die Spinnenfauna (Arachnida: Araneae) stillgelegter Abbauflächen in einem Steinbruch in Bad Deutsch-Altenburg (Österreich: Niederösterreich) - Hepner, Martin; Milasowszky, Norbert; Sigmund, Elisabeth; Waitzbauer, Wolfgang (Arachnologische Mitteilungen, 2011)

(untitled)
The epigeic spider fauna in a partially abandoned quarry in Bad Deutsch-Altenburg/ Donau (Austria: Lower Austria) was examined. Six study sites at different stages of abandonment were sampled using pitfall traps in a period from 27 March to 29 October 2006. In total, 79 species were caught comprising 845 adult individuals from 18 families. Twenty-eight species were classified as Red list taxa according to the Red lists of the Czech Republic and/or Slovakia. The poorly-known spider species Thanatus pictus L. Koch, 1881 and Xysticus embriki Kolosváry, 1935 are presented in more detail. Comparison of the six spider assemblages in the quarry with 16 geographically adjacent spider assemblages in the area of the “Parndorfer Platte” shows a clear succession within the ruderal study sites. These begin with the most recent to the oldest site, and continue to well-managed dry grasslands, further developing to scrub grasslands and hedges, and eventually to natural forests in the region.